РОЛЬ ДИСПАНСЕРИЗАЦИИ В ВЫЯВЛЕНИИ ПАТОЛОГИИ ЩИТОВИДНОЙ ЖЕЛЕЗЫ У ДЕТЕЙ - Гостимский, Александр Вадимович; Скородок, Юлия Леонидовна; Тарайкович, Анна Александровна; Передереев, Сергей Сергеевич; Иванова, Наталья Николаевна (Медицина: теория и практика, 2020)